Welsh region: River Arrow, Dreneuydd/Broadway Reen, Dysynni Low Level Drain - Dunderdale, J. A. L.; Morris, J. (National Rivers Authority, 1996)
This document describes methods, results and conclusions of a study to evaluate the impacts of alternative river maintenance strategies on the River Arrow Dreneuydd Broadway Reen and the Dysynni Low Level Drain in the Welsh Region. Its main purposes are to provide supporting information for R&D Note 456 'River Maintenance Evaluation' and to provide data which support routines for the prioritisation and programming of river maintenance.